1998
DOI: 10.1063/1.872880
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic flow physics of magnetically nozzled plasma accelerators with applications to advanced manufacturing

Abstract: The coaxial plasma accelerator is a simple, compact, and mechanically robust device that utilizes the Lorentz J×B force to accelerate plasma to high velocity. Originally developed in the 1950s for the purpose of providing energetic plasmas for fusion energy experiments, coaxial plasma accelerators are presently being investigated as an environmentally sound and economical means of materials processing and advanced manufacturing. While commercial applications of this technology are already on line, future comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…14,15 Hall-effect magnetic nozzles have accelerated helium and hydrogen plasmas to velocities of order 10 7 cm/s in a distance of 20 cm. 16 In marked contrast, a Q-machine experiment in a double-plasma-device (DPD) configuration, showed a thin double-layer electrostatic structure with 1 lower potential at the mirror point, implying rapid ion acceleration into the region of higher field strength. 17 Experiments on double layers in magnetized DPDs measured ion and electron energy distributions with gridded energy analyzers and Langmuir probes inserted into the plasma and found, even in the absence of a magnetic-field gradient, energetic ion beams attributed to spatially inhomogeneous and anisotropic EEDs.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Hall-effect magnetic nozzles have accelerated helium and hydrogen plasmas to velocities of order 10 7 cm/s in a distance of 20 cm. 16 In marked contrast, a Q-machine experiment in a double-plasma-device (DPD) configuration, showed a thin double-layer electrostatic structure with 1 lower potential at the mirror point, implying rapid ion acceleration into the region of higher field strength. 17 Experiments on double layers in magnetized DPDs measured ion and electron energy distributions with gridded energy analyzers and Langmuir probes inserted into the plasma and found, even in the absence of a magnetic-field gradient, energetic ion beams attributed to spatially inhomogeneous and anisotropic EEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma is accelerated and incorporated into the pinch continually by current in the acceleration region. The plasma accelerator operates in a "quasi-steadystate" mode that has been described previously [14].…”
mentioning
confidence: 99%
“…12,24 Lots of literature has identified that the maximum drift velocity in a magnetized plasma that is not fully ionized corresponds to the gas atom ionization energy. This velocity was called the Critical Ionization Velocity ͑CIV͒ by Alfvén.…”
Section: A Upper Stream Conditionsmentioning
confidence: 99%
“…4 -6 Modified coaxial plasma channels are also used in many other areas, such as in fusion, [7][8][9] in plasma focus, 10,11 and in material processing. 12 Ideal MHD equations have been used to understand these coaxial systems. 13 One of the most extensive studies includes a series of works by Morozov and colleagues, summarized in an excellent review.…”
Section: Introductionmentioning
confidence: 99%